Estrategias para el aprendizaje en matemática y desarrollo del pensamiento crítico en los estudiantes del primer año de bachillerato de la unidad educativa intercultural bilingüe Hualcopo Duchicela del distrito Colta-Guamote, durante el año lectivo 2015 – 2016 - Aatupaña Tocto, José Ascencio (2017)
The research problem: how active strategies for learning mathematics develop critical thinking in the first year students of Bachillerato in a Bilingual Intercultural Educational institution called “Hualcopo Duchicela” located in Columbe, in the Colta – Guamote District, during the academic year 2015 – 2016?, its general objective pretends to demonstrate how active learning strategies develop critical thinking in the first year students of Bachillerato which was cited above. The methodology applied responds to the quasi-experimental design becau two study groups were considered in the study, the experimental and the control group. The scientific method was applied for the execution of the research project and in particularly the analytical method for the theoretical bramework, the inductive and deductive methods in the classroom sessions and the application of active strategies. The synthetic method was partially applied for the alternative application of the alternative guidelines; the statistical analysis in the treatment of the results obtained after the application of the research instruments. The general hypothesis test was obtained through the application of the normalized z-statistic. It is concluded that the application of active learning strategies increases the level of development of critical thinking in students and it is recommended the daily application of these active strategies in the teaching and